Pengaruh Struktur Kepemilikan Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Studi Pada Sektor Property dan Real Estate - Sutrisno, Luky Retno Sari (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2020)
This study aims to investigate the effect of ownership on firm value with profitability as an intervening variable. The dependent variable used is PBV. While the independent variables used are managerial ownership and institutional ownership. The intervening variable used is ROA. The data in this study used an annual report from 18 property and real estate companies listed on the Indonesia Stock Exchange in 2014 to 2018. The data collection technique used purposive sampling technique obtained from the web www.idx.co.id and each website from the sample company. Data processing uses panel data regression and the results reveal that managerial ownership and institutional ownership have no effect on firm value. While profitability (ROA) is able to mediate institutional ownership of firm value. But profitability (ROA) is not able to mediate managerial ownership of firm value.